Boycott of Israel Products in Islamic Economic Perspective: An Analysis of Muslim Consumers in Makassar City - Mansyur, Fakhruddin; Malik, Abdul; Alrasyid, Harun (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2025)
This study analyzes the perceptions and actions of Muslim consumers in Makassar City towards the boycott of Israeli products in the perspective of Islamic economics. The results show that the boycott is seen as a form of solidarity with Palestine and as a manifestation of the religious, moral, and social values espoused in Islam. The main motivations for participation in the boycott include religious obligation, socio-political solidarity, social media influence, and awareness of consumer rights. The boycott led to significant changes in consumption behavior, with increased preference for local products or alternatives not associated with Israel, as well as increased awareness of product origins and adherence to halal principles. Overall, this study shows that the economic decisions of Muslim consumers in Makassar are not only based on material factors, but also on ethical and religious considerations, with boycotts seen as a way to express protest against injustice and support socio-economic change in accordance with Islamic values.